U-X-L encyclopedia of weather and natural disasters - Hackney Blackwell, Amy; Manar, Elizabeth P. (Gale virtual reference library, 2016)
Introduces students to the topic of weather and natural disasters, covering such topics as weather basics, weather phenomena, forecasting, and climate. Provides information on the scientific aspects of various types of disasters including: blizzards, earthquakes, flooding, tornadoes, volcanoes, and wildfires.